Attitude of Vegetable Growers Towards Mitigating the Ill-effects of Agricultural Chemicals - G. Manunayaka,; Ganesamoorthi, S; Goyal, Shashikant (Indian Journal of Extension Education, 2021)
The study was conducted in Kolar district of Karnataka state during 2018-19 to ascertain the attitude of vegetable growers towards mitigating the ill-effects of agricultural chemicals. The data was collected from 120vegetable growers in Kolar and Malur talukas through simple random sampling technique and pretested interview schedule. Out of the 14 independent variables chosen for the study, variables like education, riskorientation, extension participation, mass media exposure, and extension contact had positive and significant association with attitude. Other variables like age, family size, annual income, size of land holding had nosignificant association with their knowledge on the effects of agricultural chemicals. The co-efficient of determination (R2) of the independent variables was 0.790 which means that 79.09 per cent of the total variation in the attitude level was explained by the 14 selected independent variables.